Wprowadzenie w życie przepisów ustawy scaleniowej z 1933 roku w gminach wiejskich zachodniej Rzeczypospolitej - Podkowski, Marek (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
13 July 1933 was marked by the entry into force of the Act on Partial Change of the Local Government System of 23 March 1933. The most important changes introduced by the new law concerned mainly rural communes in western regions of Poland (Poznań and Pomeranian Provinces). The existing individual communes were replaced with collective communes as well as the so-called gromadas, which had not existed in the region before. At the same time the Unification Act abolished the existing administrative units (wójtostwo and estate district), with the collective rural commune, usually encompassing several localities, taking over their functions. The commune system could not be transformed within a short period. First, the authorities had to deal with the new territorial organisation of rural communes, division of communes into gromadas, new bodies to govern rural communes and gromadas, questions concerning property and settlements between the newly established rural communes and gromadas as well as rural areas.
Keywords: II Rzeczpospolita; samorząd terytorialny; gmina wiejska